Toward a communal reading of 2 Samuel 13: ideology and power within the intercultural Bible reading process - Van der Walt, Charlene (Intercultural biblical hermeneutics series, 2014)
Hermeneutical underpinnings -- Exegetical study -- Theoretical framework for the empirical study -- Research design of the empirical study -- Analysis of research results